2016
DOI: 10.1016/j.rse.2015.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the impacts of ENSO and IOD on rain gauge and remotely sensed precipitation products over Australia

Abstract: 2016. Quantifying the impacts of ENSO and IOD on rain gauge and remotely sensed precipitation products over Australia. Remote Sensing of Environment 172 , pp. (2016) Quantifying the impacts of ENSO and IOD on rain gauge and remotely sensed precipitation products over Australia. AbstractLarge-scale ocean-atmospheric phenomena like the El Niño Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) have significant influence on Australia's precipitation variability. In this study, multi-linear regression (MLR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 63 publications
3
51
1
1
Order By: Relevance
“…ENSO is a large-scale ocean-atmosphere interaction in the Tropical Pacific, which affects the climate of many regions of the Earth (Trenberth 1990;Forootan et al 2016). El Niño refers to the negative phase on ENSO, and its opposite phase is known as La Niña.…”
Section: Southern Oscillation Index (Soi)mentioning
confidence: 99%
See 2 more Smart Citations
“…ENSO is a large-scale ocean-atmosphere interaction in the Tropical Pacific, which affects the climate of many regions of the Earth (Trenberth 1990;Forootan et al 2016). El Niño refers to the negative phase on ENSO, and its opposite phase is known as La Niña.…”
Section: Southern Oscillation Index (Soi)mentioning
confidence: 99%
“…In other words, to generate a synthetic TWS data, we account for ENSO's immediate and out-of-phase influence on TWS, with a fundamental assumption that the temporal behavior of TWS changes due to ENSO is similar to SOI. This might be in reality not perfectly true (see also Forootan et al 2016), but the influence of this assumption is not strong enough to alter the results of our assessment, during which we try to measure the efficiency of decomposition techniques rather than focusing on a realistic estimation of climate impacts on geophysical data. We exclude S 2 ðtÞ and HðS 2 ðtÞÞ while fitting Eq.…”
Section: Accounting For Enso While Generating Synthetic Global Tws Datamentioning
confidence: 99%
See 1 more Smart Citation
“…• ENSO is the largest inter-annual climate variability phenomenon in the Tropical Pacific, which affects the climate of many regions of the Earth (Trenberth 1990;Forootan et al 2016). El Niño refers to the negative phase on ENSO that brings winter precipitation to the Middle East and the opposite phase La Niña causes less than normal precipitation variability (Nazemosadat and Cordery 2000).…”
Section: Climate Variability Indicesmentioning
confidence: 99%
“…Their results indicate that the TWF derived from reanalysis products might represent limited skills particularly due to biases, and the effects of anthropogenic modification that are particularly difficult to quantify (Simmons et al 2010). Compared to in situ observations, skill of the reanalyses might change from a region to another (see, e.g., Forootan et al 2016;Khandu et al 2016). On the other hand, Rodell et al (2004a) indicated that the temporal rate of changes in GRACE TWS is directly related to the changes in TWF through the water balance equation.…”
Section: Introductionmentioning
confidence: 99%